PENYUSUNAN BUKU AJAR KALIMAT EFEKTIF DENGAN PENDEKATAN RETORIK UNTUK MENINGKATKAN KUALITAS BAHASA SKRIPSI DAN TUGAS AKHIR (TA) MAHASISWA - I N. Martha; I N. Seloka Sudiara (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2012)
This research aimed at: 1) developing a textbook of effective sentences by using rhetoric approach,2) to examining this textbook to experts and users (university students). The data were gathered by means ofquestionnaire and tests, and then were analyzed descriptively and qualitatively. The results of this research are:1) A composed textbook of effective sentences by using rhetoric approach, 2) the result of examination of theexperts are that the textbook is categorized very good, and the university students are able to master effectivesentence on a good category. It is suggested that this textbook needs to be distributed to another university, anddeveloped on IT/e-learning programme.Key words: effective sentence, rhetoric approach, textbook